POLA PENINGKATAN KAPASITAS GURU MELALUI PEMBERDAYAAN GURU DI WILAYAH MINORITAS MUSLIM THAILAND - Ainiyah, Nuhzatul; Huda, Muhammad Nuril; Safriani, Afida; Awakachi, Arfal (Jurnal Isema : Islamic Educational Management, 2023)
In order to create quality of teacher, Thailand government requires the empowerment of teacher which is carried out regularly and continuously. However, Thailand consists of two parts with differences in religion, race, ethnicity, region and culture. They are Northern Thailand, known as the Kingdom of Thailand, and Southern Thailand with a majority Muslim population with a total of 80% from the three provinces of Southern Thailand, are Patani, Yala, and Narathiwat, which are known as Thailand minority. In developing and maintaining Islamic education in the region, teachers play a main role through Islamic learning. Thus, teacher empowerment becomes a crucial issue, because teachers are the main component that influence the learning process in order to achieve Islamic education. The aim of this research is to describe about the pattern of increasing teacher capacity through teacher empowerment in order to maintain Islamic education in Muslim minority areas of Thailand, as well as how teachers in Muslim minority areas are empowered by the Kingdom of Thailand. The method used for this research is a qualitative approach. This research located at the Islamic Phatna Witya School of Yala, Southern Thailand. The results of this research are that teacher empowerment at Phatna Witya School is carried out routinely through planning, implementing, and evaluation. In empowering teachers, Thai Kingdom does not discriminate between race, ethnicity, or religion. In fact, the Kingdom of Thailand upholds togetherness with the aim of improving the quality of education.